ANALISIS PENGARUH SEKTOR PERDAGANGAN, HOTEL, Dan RESTORAN TERHADAP PERTUMBUHAN EKONOMI (Studi Kasus pada Kota Surabaya) (JEB17 : Jurnal Ekonomi dan Bisnis, 2017)
Trade sector is one sector that should be developed by the local government of Surabaya. Because the trade sector is one of the largest contributors to the Gross Regional Domestic Product (PDRB) of Surabaya. Therefore, it is necessary to explore all the potential that exists in the trade sector. Trade sector can be directed to one of the achievement of development goal that is income increase in Surabaya City. With the increase in income, it is expected eventually will achieve better regional economic growth. The type of data used is quantitative data in the form of numerical calculations that prove the relationship between GDP, Trade Sector, Hotel and Restaurant in Surabaya. There are 4 variables used, namely X1 (trade sub-sector), X2 (hotel sub-sector), X3 (restaurant sub-sector) and Y (PDRB Kota Surabaya). Based on significance value at test f equal to 0,188, mean significance value 0,188> 0,05 then H0 accepted. so it can be concluded that there is a significant influence between independent variables with dependent variable at five percent real level. In the regression coefficient of trade sub-sector (PDRGt) = 1.552 and restaurant sector (RSTNt) = 1.742, the regression model is positive or one-way, that is, if the value of trade sub-sector and restaurant sub-sector is higher or increase, the value of GRDP is also higher or increase also. While the regression coefficient value of hotel sub-sector (HOTt) = -0.436 then regression model is negative or not unidirectional, it means that the increase of one percent added value of hospitality sub-sector does not cause the average increase per year PDRB Surabaya.Â Â Keywords: PDRB Kota Surabaya, Trade Sector, Regression Coefficient.